Effect of Several Types and Concentrations of Complex Organic Compounds on Growth of Pineapple In Vitro - Sianipar, Mangara W; Rustikawati, Rustikawati; Bertham, Yudhy H; Herison, Catur; Mukhtasar, Mukhtasar (Akta Agrosia, 2019)
Pineapple plants are usually propagated vegetatively by utilizing the base of the fruit (ratoone), stem buds (sucker), fruit buds (slip) and crown (crown). Propagation of plants by utilizing parts of the plant is less effective in meeting the needs because the planting material produced is small and requires a long time. An alternative to the propagation of pineapple to increase the amount of planting material is by tissue culture techniques. This study aims to obtain the best types of complex organic compounds and the right concentration for the growth of pineapple shoots in vitro. The research was conducted in June 2017 until October 2017 at the Laboratory of Agronomy at the Faculty of Agriculture, University of Bengkulu. Complete randomized design with 3 replications was used to allocate 9 treatments of complex organic compounds. The basic media used are the composition of Murashige and Skoog (MS). Treatment consists of 1) Coconut water 100 ml / l, 2) Coconut water 150 ml / l, 3) Coconut water 200 ml / l, 4) Banana porridge 100 gl / l, 5) Banana pulp 150 g / l, 6) Banana slurry 200 g / l, 7) Bean sprout extract 100 g / l, 8) Bean sprout extract 150 g / l, 9) Bean sprout extract 200 g / l. The results showed that at 16 weeks after MS media planting the addition of 100 g / l banana pulp was able to produce the highest plant height with an average of 3.45 cm. MS media with the addition of 200 ml coconut water resulted in the highest shoot height of 1.5 cm and followed by MS with the addition of 100 g / l media of banana pulp with an average of 0.9 cm. MS media with the addition of 100 ml / l of coconut water is suitable for the growth of pineapple roots with the average value of the number of roots and the highest length of roots. MS media with the addition of bean sprout extract with various concentrations is not able to stimulate shoot growth and has a growth response that tends to be slow. Keywords: Pineapple, In Vitro, Complex Organic Compounds.